Bimbingan Konseling Islam untuk Anak di Masa Pandemi - Syamsul Muqorrobin; Tamrin Fathoni (Institut Agama Islam Sunan Giri Ponorogo, 2021)
Child counseling guidance is the process of providing psychological assistance to early childhood in order to assist the early childhood in order to help the child achieve optimal development. The Islamic teaching views humans, the Koran is a source of guidance for humans in general, guidance for those who fear and guidance for those who believe, in which there is a function of dividing between right and wrong. Counseling Guidance in Islam provides a way of assistance from problems that become clients, changes in personal orientation, strengthening mental-spiritual, increasing behavior towards noble morals, improvement and other guidance and counseling techniques. Covid-19 Pandemic children's counseling guidance has become a world problem and has changed the entire human life system. In line with these changes, counseling as a science and social service must also adapt to current conditions. The research used in this writing is a study of manuscripts. The data used comes from scientific journals, scientific books, newspapers, the internet, or other written and electronic sources. The results showed that Islamic Counseling Guidance can help systematically to those in need, as well as in line with the guidance of the values ​​and principles of the teachings embodied in the Al-Qur'an and Hadith.